067 Efficacy of cladribine tablets in patients with highly active relapsing-remitting multiple sclerosis: analysis of pooled double-blind data from the clarity and onward studies. Issue 6 (24th May 2018) - Giovannoni, Gavin; Montalban, Xavier; Rammohan, Kottil; Cook, Stuart; Comi, Giancarlo; Rieckmann, Peter; Soelberg-Sorensen, Per; Vermersch, Patrick; Dangond, Fernando; King, John; Damian, Doris
Abstract : Introduction: Patients with relapsing MS (RMS) who show an increased rate of relapse or disability worsening can be described as showing high disease activity (HDA). Treatment with cladribine tablets (CT) in the CLARITY study, and with CT added to interferon-β in the ONWARD study demonstrated efficacy vs. placebo (PBO) across a range of patients with active MS. Combining double-blind data from these studies allows assessment of the efficacy of treatment with CT 3.5 mg/kg (CT3.5; cumulative dose). The objective of this post-hoc analysis is to compare the effects of CT3.5 vs. PBO on the proportion of patients achieving no evidence of disease activity (NEDA) status in HDA subgroups identified using two sets of criteria in a pooled cohort of patients from CLARITY and ONWARD. Methods: Patients from CLARITY and ONWARD were retrospectively stratified using 2 sets of HDA criteria based on relapse history, prior treatment, and MRI characteristics: high relapse activity (HRA; n=314) and HRA plus disease-activity-on-treatment (HRA +DAT; n=459). Patients treated with CT3.5 or PBO who fulfilled these criteria and achieved NEDA were compared over 2 years using odds ratios (ORs) and 95%CIs. Results: In the HRA subgroup, 76.5% of CT3.5-treated patients were relapse-free, 86.7% were T1 Gd +lesion free vs. 50.7% and 35.8%, respectively, for PBO. In the HRA +DAT subgroup, 77.6% were relapse-free and 88.8% were T1 Gd +lesion free with CT3.5 vs. 53.9% and 40.8%, respectively for PBO. In the HRA and HRA +DAT subgroups, 42.7% and 41.3%, respectively, of CT3.5-treated patients were disease activity free compared with 9.7%, (OR 6.94, 95% CI 3.67;13.12, p<0.0001) and 13.7% (OR 4.28, 95% CI 2.62;6.99, p<0.0001) respectively, of PBO recipients. In the overall CLARITY+ONWARD population (including non-HDA patients), the composite NEDA score also favoured CT over PBO (OR 3.95, 95% CI 2.90;5.37, p<0.0001). Conclusion: Compared with placebo, treatment with CT3.5 was associated with increased odds of achieving NEDA in HDA patients.